Analisis Peran dan Problematika Keluarga Terhadap Gangguan Jiwa Di Wilayah Kecamatan Kartasura - SEJATI, IMAM PROBO; , Arif Widodo, A.Kep., M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Mental disorders are a health problem that is still very important to note, it is because the patient does not have the ability to assess the reality of the poor. Symptoms and signs exhibited by people with mental disorders include cognitive disorders, thought process disturbance, disturbance of consciousness, emotional disturbances, the ability to think, and strange behavior. Cases of mental illness in Sukoharjo region in 2013 amounted to 2537 people (DHO Sukoharjo). While data from PHC Kartasura, in 2013 there were 362 patients who experienced a psychotic mental disorders with the potential amount of spread in the village Kartasura the number of 96 patients, the village Makamhaji the number 107 and in the village of Pucangan of 34 patients who made visits to the clinic. The purpose of this study was to determine the description of the role of the family and the problems of people with mental disorders in the District Kartasura. This study is a qualitative study using a phenomenological approach. Intake of informants in this study using purposive sampling technique with the number 5 with the criteria informants family of people with mental disorders. Analysis of data using models Miles and Huberman. Based on the research results, the authors conclude that : (1) Most of the family's role goes well, but there is one family that does not function well which caused mental disorders in one of the family members because the family did not give affection to their children, shouting at her and could not provide for the family (2) The problems occur in families that have a family member suffering from a mental disorder such as death of a family member, previous families have relatives who are mentally handicapped and low economic circumstances.